An NMR and MD study of complexes of bacteriophage lambda lysozyme with tetra‐ and hexa‐N‐acetylchitohexaose. Issue 1 (26th July 2019) - Turupcu, Aysegul; Bowen, Alice M.; Di Paolo, Alexandre; Matagne, André; Oostenbrink, Chris; Redfield, Christina; Smith, Lorna J.
Abstract: The X‐ray structure of lysozyme from bacteriophage lambda (λ lysozyme) in complex with the inhibitor hexa‐N‐acetylchitohexaose (NAG6) (PDB: 3D3D) has been reported previously showing sugar units from two molecules of NAG6 bound in the active site. One NAG6 is bound with four sugar units in the ABCD sites and the other with two sugar units in the E′F′ sites potentially representing the cleavage reaction products; each NAG6 cross links two neighboring λ lysozyme molecules. Here we use NMR and MD simulations to study the interaction of λ lysozyme with the inhibitors NAG4 and NAG6 in solution. This allows us to study the interactions within the complex prior to cleavage of the polysaccharide. 1 H N and 15 N chemical shifts of λ lysozyme resonances were followed during NAG4/NAG6 titrations. The chemical shift changes were similar in the two titrations, consistent with sugars binding to the cleft between the upper and lower domains; the NMR data show no evidence for simultaneous binding of a NAG6 to two λ lysozyme molecules. Six 150 ns MD simulations of λ lysozyme in complex with NAG4 or NAG6 were performed starting from different conformations. The simulations with both NAG4 and NAG6 show stable binding of sugars across the D/E active site providing low energy models for the enzyme‐inhibitor complexes. The MD simulations identify different binding subsites for the 5th and 6th sugars consistent with the NMR data. The structural information gained from the NMR experiments and MD simulations have been used to model the enzyme‐peptidoglycan complex.